Assessment of Mothers’ Knowledge and Practices Concerning Cholera at Al-Muhandiseen Region in Hilla City - Talib M. Kudhair (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To assess mothers’ knowledge and practices concerning cholera and their relationship with some sociodemographic characteristics of those mothers. Methodology: A sample of (100) mother was selected through a convenience sample for the period of July First through August 31 2007 ’؛ . Data were collected through interview of mothers were visiting PHC centers by using of constructed questionnaire developed by the researcher that contains (31) item. Reliability and Validity of the tool were determined through pilot study. A descriptive and inferential statistical approaches were used for data analysis. Results: The study indicated that mothers’ knowledge and practices concerning cholera were unacceptable and there is a significant relationship between mothers’ knowledge and practices and some of their sociodemographic characteristics such as age, level of education and economic status. Recommendations: The study recommended that an education program can be designed, constructed and implemented to mothers about the disease and further and nation-wide studies can be conducted on a large sample size of mothers.